Digital ethics in education: An examination of Omani information studies students’ ethical competencies during e-learning - Shehata, Ahmed; Khalaf, Mustafa Ali; Al-Hijji, Khalfan; Osman, Nour Eldin (Journal of Education and e-Learning Research, 2023)
Shifting to an e-learning style forced students to learn many skills and competencies to benefit from their experience in an e-learning environment. Ethical competencies play a crucial role in ensuring the fairness of students’ assessments and the overall educational process. During the COVID-19 pandemic, the research used a questionnaire to evaluate the ethical understanding of students enrolled in Sultan Qaboos University’s Information Studies Department using a quantitative methodology. The findings of this study reveal a significant lack of basic ethical competencies among students in the e-learning environment which negatively impacts their educational experience. The responses obtained indicate a low level of awareness regarding ethical practices in e-learning as well as a lack of knowledge concerning learning misconduct practices. The study suggests the implementation of an educational program that addresses academic ethical practices and e-learning misconduct across all educational levels. The outcomes of this research contribute to a better understanding of current e-learning practices among students, raise awareness about the importance of ethical competencies in e-learning and provide guidance for students to develop ethical digital competencies.